Successful Coil Embolization with Sclerotherapy for Bleeding Stomal Varices Using a Direct Percutaneous Approach: A Case Report - Sumin Park; Myung Sub Kim; Hyun Pyo Hong (Journal of the Korean Society of Radiology)
Patients with portal hypertension who have undergone stoma surgery are at risk of developing stomal varices, which can occasionally lead to bleeding. Recurrent stomal bleeding can be life-threatening; however, the optimal treatment for this condition remains unestablished due to the rarity of such varices. We report a case of a 73-year-old man with liver cirrhosis and a history of abdominoperineal resection with colostomy for rectal cancer, in whom stomal variceal bleeding was successfully treated with coil embolization and sclerotherapy via a direct percutaneous approach to the afferent vein. No re-bleeding occurred within 3 months of follow-up, and no serious complications were observed. We propose that coil embolization combined with sclerotherapy via a direct percutaneous approach is a feasible and effective treatment option for bleeding stomal varices in patients with decompensated cirrhosis.